PenerapanE-Office Dalam Rangka Mewujudkan E-Government (Studi Kasus: Biro Umum dan Protokol Setda Provinsi Bali) - Ramawati, Ni Made Indra; Pascarani, Ni Nyoman Dewi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRAK The advance of information in communication technology were developed so rapidly in the world, included in Indonesia. These development do not only affects the economics, social and culture but also touched government areas. The government developed the concept based on electronic government or known as e-government. Bali Provincial Government issued a policy of e-office application as part of the implementation of the concept. The implementation of e-office is a tool that can make government effective, efficient, transparent and accountable in providing service so people associated with the administration of correspondence in the General Affair and Protocol Bali Provincial Secretariat. The existence of the e-office is also alternative in creating good governance. This study used descriptive qualitative method. In obtaining the data, author conducted interviews with sources that are directly related to the study topics that author did. In addition, the author also conductedobservations to obtain primary data and did documents study in order to obtain secondary data. The conclusion of the study is the application of e-office showed their progress in the process of service correspondence. But the problems that must be observed is the provision of facility and infrastructure are still lacking resulting delays in administration process, still the implementation of some parts of the administration manually, the readiness of human resources, the existence of networks and servers are often susceptible to interference and lack of dissemination to the public related to the implementation of e-office. Keywords : Policy Public, Electronic Government, Electronic Office